IDEALIZATION OF REALITY THROUGH PHOTOS IN SOCIAL NETWORKS - Svetlana M. Maltseva; Natalia A. Nikitina; Ekaterina S. Surovegina (Sovremennye Issledovaniâ Socialʹnyh Problem)
With the advent of social media, there have been significant changes in people's perception of the world around them. The idealization of reality through photographs on social networks is an urgent research problem that attracts the attention of the general public. With the development of information technology, self-presentation began to be made not only in the real world, but also in the virtual world, through social networks. At the same time, one of the sides of this self-presentation is to demonstrate your life in the form of aesthetic profile photos. The research is based on such methods as comparison, analysis, synthesis and interpretation of philosophical ideas of humanists, theorists of psychoanalysis and postmodernism based on the facts of modernity. The authors suggest that the illusion of an "ideal life" destroys the natural perception of modern society about the surrounding reality and beauty. The authors conclude that the aestheticization of reality using photos on social networks has become a common practice that significantly affects how people perceive and position themselves on the Internet. The photo has ceased to be personal, confidential, and has moved into the public sphere, which is directly related to the imposition of standards and cliches. There have been changes in people's perception of the world. The goal of a person is to show his life from the point of view of idealizing reality, and not from the point of view of its realism. As we continue to navigate the digital space, it is important to keep in mind how we interact with and interpret visual content, striving for a balance between artistic expression and authentic representation.